Administracja publiczna jako kategoria ekonomiczna - Wojciechowski, Eugeniusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article deals with the economic picture of public administration. The content of the paper are comments and remarks related to chosen (in author's opinion - key) parts of public administration as an economic category. The author outlines the topic and only indicates presented problems. As the whole, the article underlines some problems and provokes to take up the discussion on this topic. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 208-220